Geotechnical and geoenvironmental characteristics of man-made underground structures in Cappadocia, Turkey - Aydan, Ömer; Ulusay, Reşat (Engineering geology, 2003)
Underground cities and semi-underground settlements, most of which are 1500 years at least, exist in the Cappadocia Region of Turkey. These man-made rock structures are carved in soft tuffs and the best examples of long-term performance of man-made structures in the field of rock engineering. The tuffs also have good thermal isolation properties to be used as housing and storage of foods. In this article, the authors are only concerned with physical and short-term mechanical characteristics due to the wide-spectrum of the theme and the in situ characterization of the Cappadocia tuffs, and the results of investigations are presented. In addition, a critical overview on possible engineering geological problems at Cappadocia with mechanical aspects of historical and modern rock structures and their implications in rock engineering is made. From the experimental results in the field, it is evident that the engineering characteristics of these rocks do not show significant changes in vertical and horizontal directions. However, they are prone to atmospheric conditions. In addition, temperature and humidity measurements at different floors of the underground cities and various parts of semi-underground settlements indicated that variations in climatic conditions of the openings are very small when compared to those outside the ground surface.